2006
DOI: 10.1186/1471-2261-6-10
|View full text |Cite
|
Sign up to set email alerts
|

T wave abnormalities, high body mass index, current smoking and high lipoprotein (a) levels predict the development of major abnormal Q/QS patterns 20 years later. A population-based study

Abstract: BackgroundMost studies on risk factors for development of coronary heart disease (CHD) have been based on the clinical outcome of CHD. Our aim was to identify factors that could predict the development of ECG markers of CHD, such as abnormal Q/QS patterns, ST segment depression and T wave abnormalities, in 70-year-old men, irrespective of clinical outcome.MethodsPredictors for development of different ECG abnormalities were identified in a population-based study using stepwise logistic regression. Anthropometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The characteristics of these studies are summarized in Tables 1 and 2. 1,2,[4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristics of these studies are summarized in Tables 1 and 2. 1,2,[4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] …”
Section: Resultsmentioning
confidence: 99%
“…Vitelli et al 10 also found that high BMI, lipoprotein(a), and glucose levels were more prevalent in those with T-wave abnormalities. Moller et al 9 examined the predictors associated with the development of major abnormal Q/QS patterns in a prospective study over 20 years, which included 2322 men aged 50 years who participated in this study. Anthropometrical and metabolic factors, ECG abnormalities, and vital signs were recorded at baseline and 20 years later.…”
Section: Associations Of Bmi With Ecg Abnormalitiesmentioning
confidence: 99%
“…2 Therefore, little epidemiologic data exist describing the association between T-wave inversion (TWI) on ECG and the prediction of ACS. 3 Most previous studies investigating risk factors for ACS are based on patients' ECGs recorded in the emergency room 4 and in hospital. 5,6 To the best of our knowledge, there are no large cohort studies showing the relationship between TWI and the risk for ACS in a general population.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the association study for each SNP with T2DM in the present Chinese population are shown in Table 3. KCNK16 rs1535500, GLIS3 rs7041847, WWOX rs17797882 and MAEA rs6815464 showed the same direction of effect (odds ratio [OR] > 1.0) as in the original reports (Sanada et al, 2012). KCNK16 rs1535500 and GLIS3 rs7041847 were associated with T2DM (rs1535500: p=0.005, OR=1.224, 95% CI 1.062-1.409; We analyzed the association of these SNPs with T2DM in the studied participants stratified by BMI.…”
Section: Resultsmentioning
confidence: 81%